Erosion and Accretion on a Mudflat: The Importance of Very Shallow‐Water Effects. Issue 12 (6th December 2017) - Shi, Benwei; Cooper, James R.; Pratolongo, Paula D.; Gao, Shu; Bouma, T. J.; Li, Gaocong; Li, Chunyan; Yang, S.L.; Wang, Ya Ping
Abstract: Understanding erosion and accretion dynamics during an entire tidal cycle is important for assessing their impacts on the habitats of biological communities and the long‐term morphological evolution of intertidal mudflats. However, previous studies often omitted erosion and accretion during very shallow‐water stages (VSWS, water depths < 0.20 m). It is during these VSWS that bottom friction becomes relatively strong and thus erosion and accretion dynamics are likely to differ from those during deeper flows. In this study, we examine the contribution of very shallow‐water effects to erosion and accretion of the entire tidal cycle, based on measured and modeled time‐series of bed‐level changes. Our field experiments revealed that the VSWS accounted for only 11% of the duration of the entire tidal cycle, but erosion and accretion during these stages accounted for 35% of the bed‐level changes of the entire tidal cycle. Predicted cumulative bed‐level changes agree much better with measured results when the entire tidal cycle is modeled than when only the conditions at water depths of >0.2 m (i.e., probe submerged) are considered. These findings suggest that the magnitude of bed‐level changes during VSWS should not be neglected when modeling morphodynamic processes. Our results are useful in understanding the mechanisms of micro‐topography formation and destruction that often occur at VSWS, and also improve our understanding and modeling ability of coastal morphological changes. Key Points: Very shallow water accounted for only 11% of the duration of the entire tidal cycle, but accounted for 35% of bed‐level changes Erosion and accretion during very shallow water stages cannot be neglected when modeling morphodynamic processes This study can improve our understanding of morphological changes of intertidal mudflats within an entire tidal cycle